Mobility [ - Adey, Peter (Key ideas in geography, 2010)
This book makes the subject of 'mobility' tangible by explaining the key theories and writings that surround it. It traces out, using an interdisciplinary approach, the concept of mobility as a key idea within the discipline of geography as well as subject areas from the wider arts and social sciences.